Antibacterial solventless coating and preparation method thereof
A solvent-free coating with a composite antibacterial agent on microspheres addresses bacterial erosion, ensuring long-lasting antibacterial performance and stability.
Patent Information
- Application Number
- CN202411659753.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Current solvent-free coatings lack effective antibacterial properties and are prone to bacterial erosion, leading to degradation and reduced service life.
A solvent-free coating comprising a composite antibacterial agent with nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate-modified nano-TiO2 adsorbed on microspheres, which are uniformly dispersed to provide broad-spectrum antibacterial performance.
The coating exhibits excellent antibacterial efficacy with a 99.99% antibacterial rate, maintaining stability for over 6 months and preventing bacterial degradation.
Smart Images

Figure CN119161798A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coatings and relates to an antibacterial solvent-free coating and a preparation method thereof. Background Art
[0002] According to the dispersion medium, currently commonly used coatings include oil-based coatings, water-based coatings and solvent-free coatings. Although oil-based coatings have mature technology and good coating quality, their biggest disadvantages are strong odor and extremely high and persistent VOC emissions. Although water-based coatings are relatively environmentally friendly and have low VOC emissions, their coating quality is poor and they are highly dependent on the environment and equipment. Therefore, the research and development of solvent-free coatings has become one of the key areas of current coating research and development work.
[0003] At present, most of the solvent-free coatings prepared do not have antibacterial properties or have poor antibacterial properties. The coatings cannot resist the erosion of bacteria or microorganisms for a long time. The corrosion phenomenon in the coatings will gradually intensify. With the continuous reproduction of microorganisms, the pollution and degradation of the coating surface will become more and more serious, and even the coating film may peel off or fall off, which will eventually shorten the service life of the coating. Summary of the invention
[0004] The purpose of the present invention is to provide an antibacterial solvent-free coating and a preparation method thereof, so as to solve the problem that there is currently no solvent-free coating with good antibacterial performance and low VOC emission.
[0005] The technical solution adopted by the present invention is as follows: An antibacterial solvent-free coating comprises component A and component B; The component A comprises the following components in parts by weight: 45-70 parts of vegetable oil-based modified polyol, 0.5-1.5 parts of antibacterial agent, 20-40 parts of pigment and filler, and 4-8 parts of film-forming aid; The component B is a silane-modified terminal isocyanate prepolymer; The mass ratio of component A to component B is (2~2.4):1; The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; The mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier is 3:2:5; The surface porosity of the microspheres is 30%-60%, the particle size D90 of the microspheres is 10-15 μm, the particle size D90 of nano-grade zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 are both 50-80 nm, and the pore size of the microsphere surface pores is 50-100 nm.
[0006] The surface porosity of the microspheres in the present invention is 30%-60%, which refers to the distribution width of the surface porosity of all microspheres participating in the reaction. The distribution width is 30%-60%, which means that a large number of microspheres participating in the reaction have a surface porosity of 30% or 40% or 50% or 60% or all of the above.
[0007] In the present invention, the particle size D90 of the microspheres is 10-15 μm, which means that 90% of all the microspheres participating in the reaction have a particle size of 10-15 μm. Similarly, the particle size D90 of the nano-scale zinc-loaded hydroxyapatite and the nano-TiO2 modified by ammonium cerium nitrate is 50-80 nm, which means that 90% of all the nano-scale zinc-loaded hydroxyapatite and the nano-TiO2 modified by ammonium cerium nitrate participating in the reaction have a particle size of 50-80 nm; the pore size of the microsphere surface pores is 50-100 nm, which means that the particle size distribution of the pores on the surface of a single microsphere is within a width range of 50-100 nm.
[0008] In the present invention, component B is a curing agent for component A. Component A and component B are uniformly mixed to obtain an antibacterial coating. After the components A and B are mixed, a cross-linking curing reaction occurs. The main reaction mechanism for imparting the properties of the paint film is: —N=C=O + HO - = —NH—COO - ; Hydroxyapatite is a carrier of zinc ions, which can cause bacterial death or abnormal growth through physical destruction, charge action, or by promoting the generation of reactive oxygen species, inhibiting enzyme activity, interfering with gene expression, etc. The specific explanation is: Physical destruction: The high specific surface area of nanoparticles enables them to directly contact the bacterial cell membrane and destroy its structure, leading to bacterial death.
[0009] Charge effect: Zinc ions can combine with negatively charged molecules on bacterial cell membranes through electrostatic attraction, interfering with cell membrane function and affecting the normal physiological activities of bacteria.
[0010] Reactive oxygen generation: Zinc particles can catalyze the production of highly oxidizing reactive oxygen species, which can destroy the cell structure of bacteria and cause bacterial death.
[0011] Inhibit enzyme activity: Zinc ions can bind to a variety of enzymes in bacteria, inhibit their activity, and block the normal growth and metabolic pathways of bacteria.
[0012] Interference with gene expression: Zinc ions can interfere with gene expression by affecting bacterial DNA replication and transcription, thereby inhibiting bacterial growth.
[0013] Nano-TiO2 is a photocatalytic semiconductor material. When irradiated by ultraviolet light, the valence electrons will be excited to the conduction band, thereby generating highly active photogenerated electron-hole pairs. These pairs have strong redox properties and can destroy the cell structure of bacteria, leading to bacterial death.
[0014] The antibacterial agent prepared by loading zinc ions on hydroxyapatite has the antibacterial effect of metal ions, and nano-TiO2 has a photocatalytic antibacterial effect. The composite antibacterial agent of the present invention organically combines the photocatalytic decomposition of bacteria and the antibacterial effect of metal ions, and exhibits ultra-high efficiency antibacterial performance both indoors and outdoors.
[0015] In addition, the present invention uses microspheres as carriers to adsorb nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate on the surface thereof to form a composite antibacterial material, thereby avoiding the dispersion of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate in the coating separately. Since the antibacterial properties of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are different, if nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are independently dispersed in the coating separately, some parts of the coating will not have nano-TiO2 modified by ammonium cerium nitrate or nano-scale zinc-loaded hydroxyapatite, which will have an adverse effect on the antibacterial properties of the coating. Therefore, the present invention selects microspheres as carriers, and the minimum unit of the composite antibacterial material formed by the simultaneous adsorption of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 on the microspheres is a microsphere surface on which nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 are simultaneously adsorbed. The microspheres are uniformly dispersed in the coating under the action of the dispersant, and the coating formed after the microspheres are uniformly dispersed in the coating has the dual antibacterial properties of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 in basically every part; in the present invention, the adsorption amount of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 by a single microsphere has little effect on the antibacterial effect, because multiple microspheres are distributed on the coating, and the synergistic effect of multiple microspheres can have a better antibacterial effect on the corresponding parts.
[0016] The addition of ammonium cerium nitrate in the present invention inhibits the growth of nano-TiO2 grains, so that it maintains a smaller grain size. A smaller grain size means a higher specific surface area and more surface atoms, thereby improving the efficiency of the photocatalytic reaction. This is because more surface atoms can provide more reaction sites, making it easier for photogenerated electrons and holes to react with surrounding oxygen and water molecules to generate more active oxygen species; therefore, ammonium cerium nitrate-modified nano-TiO2 enhances the antibacterial properties of TiO2.
[0017] The antibacterial coating of the present invention has the advantages of broad-spectrum antibacterial property, excellent antibacterial performance, and long-lasting and stable antibacterial effect. According to the test requirements of GB / T 21866-2008 standard, the antibacterial rate of the antibacterial coating prepared by the present invention is greater than 99.99%. The solvent-free antibacterial coating of the present invention can be stably stored for more than 6 months, and the coating has excellent stability and high-efficiency antibacterial property.
[0018] Furthermore, the composite antibacterial agent is prepared by the following method: S1. Preparation of intermediate carrier S1.1, preparation of solid microspheres: polylactic acid-polymethyl methacrylate block copolymer and polyethylene glycol are dissolved in dichloromethane, and calcium sulfate is added after stirring evenly, and stirred evenly to obtain a polymer solution; the polymer solution is slowly added dropwise to the aqueous phase containing polyvinyl alcohol, and emulsified by ultrasonic emulsifier at room temperature to form a stable O / W type emulsion; the O / W type emulsion is placed at 30-40°C to volatilize the solvent, and when the solvent is completely evaporated, the microspheres are separated from the emulsion by a centrifuge, the microspheres are washed with deionized water for multiple times, and then dried to obtain solid microspheres; S1.2, surface pore formation: soak the solid microspheres in phosphoric acid etchant, etch at 25°C for 30-40 minutes, wash and dry to obtain solid microspheres with pores distributed on the surface; S1.3, microsphere surface modification: firstly, 3-(acryloyloxy)propyltrimethoxysilane is prepared into a silane coupling agent solution with a mass fraction of 1.2%, and then the solid microspheres with pores on the surface are immersed in the silane coupling agent solution, and the microspheres are taken out after keeping for 2 hours and dried at 60°C for 1 hour to obtain microspheres modified by silane coupling agent; then, the photosensitive compound is dissolved in chloroform to obtain a photosensitive compound solution, and then the silane coupling agent-modified microspheres are immersed in the photosensitive compound solution and reacted at room temperature for 7-8 hours, and then filtered and dried to obtain solid microspheres with pores on the surface after surface modification by 3-(acryloyloxy)propyltrimethoxysilane and photosensitive compound, wherein the solid microspheres with pores on the surface after surface modification are intermediate carriers; wherein, the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system; S2, preparing nano-scale zinc-loaded hydroxyapatite; S3, preparing ammonium cerium nitrate modified nano-TiO2; S4. Place nano-TiO2 modified by ammonium cerium nitrate and nano-zinc-loaded hydroxyapatite in anhydrous ethanol solution, disperse by ultrasonication to form a uniform suspension, add the intermediate carrier into the suspension, stir continuously for 10-12 hours at 30°C, filter and dry to obtain microspheres with nano-zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate adsorbed on the surface, which is the composite antibacterial agent.
[0019] The present invention adopts polylactic acid-polymethyl methacrylate block copolymer as the raw material for preparing microspheres, and utilizes the good biocompatibility and excellent temperature resistance of polylactic acid-polymethyl methacrylate block copolymer. Because the curing reaction of coating component A and component B in the present invention is an exothermic reaction, in order to avoid the adverse effect of the temperature rise of the curing reaction on the stability of the microspheres, the present invention selects polylactic acid-polymethyl methacrylate block copolymer with good temperature resistance as the raw material for preparing microspheres; polyethylene glycol and calcium sulfate are added in the process of preparing microspheres, and polyethylene glycol and calcium sulfate are pore inhibitors, which can reduce the porosity inside the microspheres, and the internal porosity of the solid microspheres finally obtained is very low; due to the microspheres adsorbing nitric acid If there are too many pores inside the nano-TiO2 modified by ammonium cerium and the nano-scale zinc-loaded hydroxyapatite, the nano-TiO2 modified by ammonium cerium nitrate and the nano-scale zinc-loaded hydroxyapatite will enter the microspheres, and the microspheres will hinder the response of the nano-TiO2 modified by ammonium cerium nitrate to light, causing an adverse effect on the photocatalytic reaction thereof; the microspheres will hinder the release of zinc ions in the nano-scale zinc-loaded hydroxyapatite and its contact with bacteria; therefore, the present invention prepares solid microspheres with small internal porosity; then pores are formed on the surface of the microspheres, so that the nano-TiO2 modified by ammonium cerium nitrate and the nano-scale zinc-loaded hydroxyapatite are adsorbed on the surface of the microspheres, reducing the influence of the microspheres on the antibacterial properties of the nano-TiO2 modified by ammonium cerium nitrate and the nano-scale zinc-loaded hydroxyapatite.
[0020] The present invention adopts 3-(acryloyloxy)propyltrimethoxysilane to modify the interface of the microspheres, thereby enhancing the adsorption firmness of the ammonium cerium nitrate modified nano-TiO2, the nano-grade zinc-carrying hydroxyapatite and the microspheres; the present invention also adopts a photosensitive compound to modify the surface of the microspheres, which is equivalent to adding a photosensitive compound to the carrier of the ammonium cerium nitrate modified nano-TiO2. When the photosensitive compound is exposed to light, it transfers the absorbed light energy to the ammonium cerium nitrate modified nano-TiO2, thereby stimulating more electron transitions inside the ammonium cerium nitrate modified nano-TiO2, which increases the number of photogenerated electrons and holes on the surface of titanium dioxide, thereby improving its ability to generate free radicals, so that the antibacterial property of the ammonium cerium nitrate modified nano-TiO2 is better.
[0021] Furthermore, the amount of polyethylene glycol added is 5% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, the amount of calcium sulfate added is 1% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, and the concentration of polyvinyl alcohol is 0.5wt%.
[0022] Furthermore, the phosphoric acid etchant is composed of the following components in mass fractions: 25% phosphoric acid, 58% citric acid, 1% surfactant, and the balance is deionized water.
[0023] Furthermore, the preparation method of the nano-scale zinc-loaded hydroxyapatite is: preparing hydroxy titanium phosphate by coprecipitation reaction with calcium nitrate, disodium hydrogen phosphate and titanium sulfate, and then preparing the nano-scale zinc-loaded hydroxy titanium phosphate by ion exchange method with zinc ions.
[0024] Furthermore, the ammonium cerium nitrate modified nano-TiO2 is prepared by the following method: adding appropriate amounts of anhydrous ethanol, hydrochloric acid and butyl titanate into a three-necked flask, and ultrasonically dispersing for 30 minutes to form a titanium source solution; dissolving the ammonium cerium nitrate in ethanol and stirring evenly to obtain a modifier solution; under stirring conditions, slowly dropping the modifier solution into the titanium source solution, mixing and stirring at a speed of 500-800 r / min for 2-4 hours to obtain a transparent sol, and after drying and grinding the transparent sol, calcining at 800°C for 5 hours in a nitrogen atmosphere to obtain the ammonium cerium nitrate modified nano-TiO2.
[0025] Furthermore, the component B is prepared by the following method: adding a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stirring at 90-120° C. for 1-2 h, then transferring to a reactor with a vacuum device, increasing the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, maintaining at 180-220° C. for 2-3 h, cooling to room temperature, and then transferring back to the four-necked flask; subsequently, stirring under the protection of dry nitrogen, slowly dropping isophorone diisocyanate, an organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine into the four-necked flask, raising the temperature to 60 to 90° C. after the addition is complete, maintaining for 2-3 h, then cooling to room temperature, and discharging to obtain a silane-modified terminal isocyanate prepolymer.
[0026] Furthermore, the pigment filler in component A includes the following components in parts by weight: 15-25 parts of titanium dioxide with a particle size of 800 mesh, 5-15 parts of talc with a particle size of 3000 mesh, and 5-15 parts of heavy calcium with a particle size of 1250 mesh; The film-forming aid comprises the following components in parts by weight: 0.2-0.4 parts of an organosilicon defoamer, 1-2 parts of a wetting and leveling agent, 1-2.5 parts of a dispersant, 2-3.5 parts of a retarder, and 1.5-3 parts of an adhesion promoter; The component A is prepared by the following method: placing a vegetable oil-based modified polyol and a dispersant in a high-speed disperser, mechanically stirring for 5-10 minutes at a speed of 500-700 r / min, then slowly dropping an organic defoamer into the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser, mechanically stirring for 50-90 minutes at a speed of 1200-1500 r / min, wherein the slurry temperature does not exceed 60° C. during the stirring process, then adding a wetting and leveling agent, a retarder, and an adhesion enhancer, mechanically stirring for 10-30 minutes at a speed of 500-700 r / min, obtaining a crude product, and then filtering the crude product through a 150-mesh gauze and packaging it to obtain component A.
[0027] Further, an antibacterial solvent-free coating comprises component A and component B; The component A comprises the following components in parts by weight: 70 parts of vegetable oil-based modified polyol, 1.5 parts of antibacterial agent, 40 parts of pigment and filler, and 8 parts of film-forming aid; The component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is 2.2:1; The antibacterial agent in the component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and the intermediate carrier is 3:2:5; the surface porosity of the microsphere is 30%-60%, the particle size D90 of the microsphere is 10-15μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are both 50-80nm, and the pore size of the pores on the surface of the microsphere is 50-100nm; The film-forming aid comprises the following components in parts by weight: 0.3 parts of an organosilicon defoamer, 1.5 parts of a wetting and leveling agent, 1.5 parts of a dispersant, 2.5 parts of a retarder, and 2 parts of an adhesion promoter; The pigments and fillers in component A include the following components in parts by weight: 20 parts of titanium dioxide with a particle size of 800 mesh, 10 parts of talc with a particle size of 3000 mesh, and 10 parts of heavy calcium with a particle size of 1250 mesh.
[0028] A method for preparing an antibacterial solvent-free coating comprises the following steps: A. Synthesis of component A: Place the vegetable oil-based modified polyol and dispersant in a high-speed disperser, stir mechanically for 5-10 minutes at a speed of 500-700 r / min, then slowly drop the organic defoamer into the mixture, continue to stir and mix in the high-speed disperser for 10 minutes, then add the antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser in sequence, stir mechanically for 50-90 minutes at a speed of 1200-1500 r / min, the slurry temperature does not exceed 60°C during the stirring process, then add the wetting and leveling agent, retarder, and adhesion enhancer, stir mechanically for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filter the crude product through a 150-mesh gauze and package it to obtain component A; B. Synthesis of component B: Add the vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stir at 90-120°C for 1-2 h, transfer to a reactor equipped with a vacuum pump, increase the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, keep at 180-220°C for 2-3 h, cool to room temperature, and transfer back to the four-necked flask; then, stir under the protection of dry nitrogen, slowly drop isophorone diisocyanate, organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine into the four-necked flask, raise the temperature to 60 to 90°C after the addition is complete, keep for 2-3 h, then cool to room temperature, and discharge the material to obtain a silane-modified terminal isocyanate prepolymer; C. Component A and component B are uniformly mixed to obtain an antibacterial solvent-free coating.
[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The antibacterial solvent-free coating of the present invention uses microspheres as carriers, and simultaneously adsorbs nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate-modified nano-TiO2 to form a composite antibacterial material. After the microspheres are evenly dispersed in the coating, the coating formed has the dual antibacterial properties of nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate-modified nano-TiO2 in almost every part; 2. The present invention prepares solid microspheres with small internal porosity; then pores are formed on the surface of the microspheres, so that ammonium cerium nitrate-modified nano-TiO2 and nano-grade zinc-loaded hydroxyapatite are adsorbed on the surface of the microspheres, thereby reducing the influence of the microspheres on the antibacterial properties of ammonium cerium nitrate-modified nano-TiO2 and nano-grade zinc-loaded hydroxyapatite; 3. The present invention uses polylactic acid-polymethyl methacrylate block copolymer as the raw material for preparing microspheres, and utilizes the good biocompatibility and excellent temperature resistance of polylactic acid-polymethyl methacrylate block copolymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative work, among which: Figure 1 is a SEM scanning electron microscope image of the solid microspheres in Example 1 of the present invention; Figure 2 is a cross-sectional SEM scanning electron microscope image of the solid microsphere in Example 1 of the present invention; Figure 3 is a SEM scanning electron microscope image of a solid microsphere with pores distributed on the surface after pore formation in Example 1 of the present invention; Figure 4 is a cross-sectional SEM scanning electron microscope image of the solid microspheres prepared in Comparative Example 12 of the present invention; Figure 5 is a cross-sectional SEM scanning electron microscope image of a solid microsphere having pores distributed on the surface after pore formation in Example 1 of the present invention; Figure 6 This is a SEM scanning electron microscope image of the surface of the microspheres of the composite antibacterial agent in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.
[0032] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0033] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0034] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0035] An antibacterial solvent-free coating comprises component A and component B; The component A comprises the following components in parts by weight: 45-70 parts of vegetable oil-based modified polyol, 0.5-1.5 parts of antibacterial agent, 20-40 parts of pigment and filler, and 4-8 parts of film-forming aid; the vegetable oil-based modified polyol adopts a vegetable oil-based modified polyol with a functionality of 2 or 3 and a relative molecular weight of less than 2000, such as Vantelus D2000 modified castor oil polyol or Puranol D210 vegetable oil-based modified polyol; The component B is a silane-modified terminal isocyanate prepolymer; The mass ratio of component A to component B is (2~2.4):1; The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; The mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier is 3:2:5; The surface porosity of the microspheres is 30%-60%, the particle size D90 of the microspheres is 10-15 μm, the particle size D90 of nano-grade zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 are both 50-80 nm, and the pore size of the microsphere surface pores is 50-100 nm.
[0036] The composite antibacterial agent is prepared by the following method: S1. Preparation of intermediate carrier S1.1, preparation of solid microspheres: polylactic acid-polymethyl methacrylate block copolymer and polyethylene glycol are dissolved in dichloromethane, and calcium sulfate is added after stirring evenly, and stirred evenly to obtain a polymer solution; the polymer solution is slowly added dropwise to the aqueous phase containing polyvinyl alcohol, and emulsified by ultrasonic emulsifier at room temperature to form a stable O / W type emulsion; the O / W type emulsion is placed at 30-40°C to volatilize the solvent, and when the solvent is completely volatilized, the microspheres are separated from the emulsion by a centrifuge, the microspheres are washed with deionized water for multiple times, and then dried to obtain solid microspheres; S1.2, surface pore formation: solid microspheres are immersed in phosphoric acid etchant, etched at 25°C for 30 minutes, washed and dried to obtain solid microspheres with pores distributed on the surface; the porosity of the microsphere surface after etching with the etchant of the present invention can reach 30-60%, and the adsorption effect is better only when the porosity is higher than 30%. It is difficult to achieve a porosity exceeding 60% because, when the surface porosity exceeds 60%, the inside of the microsphere will be etched to a certain extent.
[0037] S1.3, microsphere surface modification: firstly, 3-(acryloyloxy)propyltrimethoxysilane is prepared into a silane coupling agent solution with a mass fraction of 1.2%, and then the solid microspheres with pores on the surface are immersed in the silane coupling agent solution, and the microspheres are taken out after keeping for 2 hours and dried at 60°C for 1 hour to obtain microspheres modified by silane coupling agent; then, the photosensitive compound is dissolved in chloroform to obtain a photosensitive compound solution, and then the microspheres modified by silane coupling agent are immersed in the photosensitive compound solution and reacted at room temperature for 7-8 hours, and then filtered and dried to obtain solid microspheres with pores on the surface after surface modification by 3-(acryloyloxy)propyltrimethoxysilane and photosensitive compound, wherein the solid microspheres with pores on the surface after surface modification are intermediate carriers; wherein, the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system; S2, preparing nano-scale zinc-loaded hydroxyapatite; S3, preparing ammonium cerium nitrate modified nano-TiO2; S4. Place nano-TiO2 modified by ammonium cerium nitrate and nano-zinc-loaded hydroxyapatite in anhydrous ethanol solution, disperse by ultrasonication to form a uniform suspension, add the intermediate carrier into the suspension, stir continuously for 10-12 hours at 30°C, filter and dry to obtain microspheres with nano-zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate adsorbed on the surface, which is the composite antibacterial agent.
[0038] The amount of polyethylene glycol added is 5% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, the amount of calcium sulfate added is 1% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, and the concentration of polyvinyl alcohol is 0.5wt%.
[0039] The phosphoric acid etchant is composed of the following components by mass fraction: 25% phosphoric acid, 58% citric acid, 1% surfactant, and the balance is deionized water. The preparation method of the phosphoric acid etchant is: add weighed phosphoric acid and citric acid into a mixing container in sequence, add deionized water, stir thoroughly with a stirring device until the phosphoric acid and citric acid are completely dissolved, then add the surfactant, continue stirring until completely dispersed, and obtain the phosphoric acid etchant; wherein the surfactant can be sodium dodecane alkyl sulfonate.
[0040] The preparation method of the nano-scale zinc-loaded hydroxyapatite is: prepare hydroxy titanium phosphate by coprecipitation reaction with calcium nitrate, disodium hydrogen phosphate and titanium sulfate, and then prepare the nano-scale zinc-loaded hydroxy titanium phosphate by ion exchange method. Nano-scale zinc-loaded hydroxy apatite is a prior art, and the preparation method is also a prior art.
[0041] The ammonium cerium nitrate modified nano-TiO2 is prepared by the following method: adding appropriate amounts of anhydrous ethanol, hydrochloric acid and butyl titanate into a three-necked flask, and ultrasonically dispersing for 30 minutes to form a titanium source solution; dissolving the ammonium cerium nitrate in ethanol and stirring evenly to obtain a modifier solution; under stirring conditions, slowly dropping the modifier solution into the titanium source solution, mixing and stirring at a speed of 500-800 r / min for 2-4 hours to obtain a transparent sol, and after drying and grinding the transparent sol, calcining at 800°C for 5 hours in a nitrogen atmosphere to obtain the ammonium cerium nitrate modified nano-TiO2.
[0042] The component B is prepared by the following method: adding a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stirring at 90-120° C. for 1-2 h, then transferring to a reactor equipped with a vacuum pump, increasing the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, maintaining at 180-220° C. for 2-3 h, cooling to room temperature, and then transferring back to the four-necked flask; subsequently, stirring under the protection of dry nitrogen, slowly dropping isophorone diisocyanate, an organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine into the four-necked flask, raising the temperature to 60 to 90° C. after the addition is complete, maintaining for 2-3 h, then cooling to room temperature, and discharging to obtain a silane-modified terminal isocyanate prepolymer. The vegetable oil-based modified polyol used to prepare component B and the vegetable oil-based modified polyol in component A may be the same substance.
[0043] The pigment filler in component A includes the following components in parts by weight: 15-25 parts of titanium dioxide with a particle size of 800 mesh, 5-15 parts of talc with a particle size of 3000 mesh, and 5-15 parts of heavy calcium with a particle size of 1250 mesh; The film-forming aid comprises the following components in parts by weight: 0.2-0.4 parts of an organosilicon defoamer, 1-2 parts of a wetting and leveling agent, 1-2.5 parts of a dispersant, 2-3.5 parts of a retarder, and 1.5-3 parts of an adhesion promoter; wherein the organosilicon defoamer may be a polydimethylsiloxane organosilicon defoamer, the wetting and leveling agent may be DHX-104E, DHX-04 or LW-604, the dispersant may be a dispersant such as DISPERBYK-2008 or DISPERBYK-110, the retarder may be citric acid or tartaric acid or sodium methyl tartrate, and the adhesion promoter may be PEAP 1600 or PEAP 1611; The component A is prepared by the following method: placing a vegetable oil-based modified polyol and a dispersant in a high-speed disperser, mechanically stirring for 5-10 minutes at a speed of 500-700 r / min, then slowly dropping an organic defoamer into the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser, mechanically stirring for 50-90 minutes at a speed of 1200-1500 r / min, wherein the slurry temperature does not exceed 60° C. during the stirring process, then adding a wetting and leveling agent, a retarder, and an adhesion enhancer, mechanically stirring for 10-30 minutes at a speed of 500-700 r / min, obtaining a crude product, and then filtering the crude product through a 150-mesh gauze and packaging it to obtain component A.
[0044] Preferably, an antibacterial solvent-free coating comprises component A and component B; The component A comprises the following components in parts by weight: 70 parts of vegetable oil-based modified polyol, 1.5 parts of antibacterial agent, 40 parts of pigment and filler, and 8 parts of film-forming aid; The component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is 2.2:1; The antibacterial agent in the component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and the intermediate carrier is 3:2:5; the surface porosity of the microsphere is 30%-60%, the particle size D90 of the microsphere is 10-15μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are both 50-80nm, and the pore size of the pores on the surface of the microsphere is 50-100nm; The film-forming aid comprises the following components in parts by weight: 0.3 parts of an organosilicon defoamer, 1.5 parts of a wetting and leveling agent, 1.5 parts of a dispersant, 2.5 parts of a retarder, and 2 parts of an adhesion promoter; The pigments and fillers in component A include the following components in parts by weight: 20 parts of titanium dioxide with a particle size of 800 mesh, 10 parts of talc with a particle size of 3000 mesh, and 10 parts of heavy calcium with a particle size of 1250 mesh.
[0045] A method for preparing an antibacterial solvent-free coating comprises the following steps: A. Synthesis of component A: Place the vegetable oil-based modified polyol and dispersant in a high-speed disperser, stir mechanically for 5-10 minutes at a speed of 500-700 r / min, then slowly drop the organic defoamer into the mixture, continue to stir and mix in the high-speed disperser for 10 minutes, then add the antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser in sequence, stir mechanically for 50-90 minutes at a speed of 1200-1500 r / min, the slurry temperature does not exceed 60°C during the stirring process, then add the wetting and leveling agent, retarder, and adhesion enhancer, stir mechanically for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filter the crude product through a 150-mesh gauze and package it to obtain component A; B. Synthesis of component B: Add the vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stir at 90-120°C for 1-2 h, transfer to a reactor equipped with a vacuum pump, increase the vacuum degree to -0.08 ~ -0.12 MPa at a rate of -0.02 MPa / h, keep at 180-220°C for 2-3 h, cool to room temperature, and transfer back to the four-necked flask; then, under the protection of dry nitrogen, slowly add isophorone diisocyanate, organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine dropwise to the four-necked flask, raise the temperature to 60 ~ 90°C after the addition is complete, keep for 2-3 h, then cool to room temperature, and discharge the material to obtain a silane-modified terminal isocyanate prepolymer; wherein the organic bismuth metal catalyst may be tributyl bismuth, triisopropyl bismuth, or bismuth isooctanoate.
[0046] C. Component A and component B are uniformly mixed to obtain an antibacterial solvent-free coating.
[0047] Example 1 A preferred embodiment of the present invention provides an antibacterial solvent-free coating, comprising component A and component B; The component A comprises the following components in parts by weight: 70 parts of vegetable oil-based modified polyol, 1.5 parts of antibacterial agent, 40 parts of pigment and filler, and 8 parts of film-forming aid; wherein the vegetable oil-based modified polyol is Vantelus D2000 modified castor oil polyol, and the vegetable oil-based plasticizer is acetyl tributyl citrate; The component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is 2.2:1; The antibacterial agent in the component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and the intermediate carrier is 3:2:5; the surface porosity of the microsphere is 30%-60%, the particle size D90 of the microsphere is 10-15μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are both 50-80nm, and the pore size of the pores on the surface of the microsphere is 50-100nm; The preparation method of the composite antibacterial agent is: S1. Preparation of intermediate carrier S1.1, preparation of solid microspheres: polylactic acid-polymethyl methacrylate block copolymer and polyethylene glycol are dissolved in dichloromethane, stirred evenly, and then calcium sulfate is added, and stirred evenly to obtain a polymer solution; the polymer solution is slowly added dropwise to the aqueous phase containing polyvinyl alcohol, and emulsified by ultrasonic emulsifier at room temperature to form a stable O / W type emulsion; the O / W type emulsion is placed at 30-40°C to evaporate the solvent, and when the solvent is completely evaporated, the microspheres are separated from the emulsion by a centrifuge, and the microspheres are washed with deionized water for multiple times, and then dried to obtain solid microspheres; the amount of polyethylene glycol added is 5% of the mass of polylactic acid-polymethyl methacrylate block copolymer, the amount of calcium sulfate added is 1% of the mass of polylactic acid-polymethyl methacrylate block copolymer, and the concentration of polyvinyl alcohol is 0.5wt%; The SEM scanning electron microscope image of the solid microspheres is as follows Figure 1 As shown, the cross-sectional SEM scanning electron microscope image of the solid microsphere is as follows Figure 2 shown; combined Figure 1 , Figure 2 As shown, the solid microspheres in the present invention are solid microsphere structures with low internal porosity; S1.2, surface pore formation: soak the solid microspheres in a phosphoric acid etchant, etch at 25°C for 40 minutes, wash and dry to obtain solid microspheres with pores distributed on the surface; the phosphoric acid etchant is composed of the following components by mass fraction: 25% phosphoric acid, 58% citric acid, 1% surfactant, and the balance is deionized water; The SEM scanning electron microscope image of solid microspheres with pores on the surface is shown in Figure 3 As shown, the surface of the obtained microspheres is distributed with voids; the cross-sectional SEM scanning electron micrograph of the solid microspheres with voids on the surface is shown in Figure 5 As shown. Figure 2 and Figure 5It can be seen that the pores inside the microspheres after etching have not changed significantly, indicating that no etching has occurred inside the microspheres.
[0048] S1.3, microsphere surface modification: firstly, 3-(acryloyloxy)propyltrimethoxysilane is prepared into a silane coupling agent solution with a mass fraction of 1.2%, and then the solid microspheres with pores on the surface are immersed in the silane coupling agent solution, and the microspheres are taken out after keeping for 2 hours and dried at 60°C for 1 hour to obtain microspheres modified by silane coupling agent; then, the photosensitive compound is dissolved in chloroform to obtain a photosensitive compound solution, and then the microspheres modified by silane coupling agent are immersed in the photosensitive compound solution and reacted at room temperature for 7-8 hours, and then filtered and dried to obtain solid microspheres with pores on the surface after surface modification by 3-(acryloyloxy)propyltrimethoxysilane and photosensitive compound, wherein the solid microspheres with pores on the surface after surface modification are intermediate carriers; wherein, the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system; S2. Preparation of nano-scale zinc-loaded hydroxyapatite: preparing hydroxy titanium phosphate by coprecipitation reaction with calcium nitrate, disodium hydrogen phosphate and titanium sulfate, dispersing the prepared hydroxy titanium phosphate in deionized water to form a suspension, and then slowly dropping a zinc sulfate solution into the suspension to allow zinc ions to undergo ion exchange reaction with calcium ions in the hydroxy titanium phosphate to obtain nano-scale zinc-loaded hydroxy apatite; this method is a prior art, and the detailed steps are not described here; S3. Preparation of ammonium cerium nitrate modified nano-TiO2: Add appropriate amount of anhydrous ethanol, hydrochloric acid and butyl titanate into a three-necked flask, and form a titanium source solution after ultrasonic dispersion for 30 minutes; dissolve ammonium cerium nitrate in ethanol and stir evenly to obtain a modifier solution; under stirring conditions, slowly drop the modifier solution into the titanium source solution, mix and stir at a speed of 500-800 r / min for 2-4 hours to obtain a transparent sol, and after drying and grinding the transparent sol, calcine at 800°C for 5 hours under a nitrogen atmosphere to obtain ammonium cerium nitrate modified nano-TiO2; S4. Place ammonium cerium nitrate modified nano-TiO2 and nano-zinc-loaded hydroxyapatite in anhydrous ethanol solution, disperse by ultrasonication to form a uniform suspension, then add the intermediate carrier to the suspension, continue stirring at 30°C for 10-12 hours, filter and dry to obtain microspheres with nano-zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 adsorbed on the surface, which is the composite antibacterial agent; the SEM scanning electron microscope image of the microsphere surface of the composite antibacterial agent is as follows Figure 6 As shown, there are obviously particles adhered to the surface; The film-forming aid comprises the following components in parts by weight: 0.3 parts of silicone defoamer, 1.5 parts of wetting and leveling agent, 1.5 parts of dispersant, 2.5 parts of retarder, and 2 parts of adhesion promoter; the silicone defoamer is a polydimethylsiloxane silicone defoamer, the wetting and leveling agent is DHX-104E, the dispersant is DISPERBYK-2008 dispersant, the retarder is citric acid, and the adhesion promoter is PEAP 1600.
[0049] The pigments and fillers in component A include the following components in parts by weight: 20 parts of titanium dioxide with a particle size of 800 mesh, 10 parts of talc with a particle size of 3000 mesh, and 10 parts of heavy calcium with a particle size of 1250 mesh.
[0050] A method for preparing an antibacterial solvent-free coating comprises the following steps: A. Synthesis of component A: Place the vegetable oil-based modified polyol and dispersant in a high-speed disperser, stir mechanically for 5 minutes at a speed of 700 r / min, then slowly drop the organic defoamer into the mixture, continue to stir and mix in the high-speed disperser for 10 minutes, then add the antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser in sequence, stir mechanically for 50 minutes at a speed of 1500 r / min, the slurry temperature during the stirring process is 50°C, then add the wetting and leveling agent, retarder, and adhesion enhancer, stir mechanically for 10 minutes at a speed of 700 r / min to obtain a crude product, and then filter the crude product through a 150-mesh gauze and package it to obtain component A; B. Synthesis of component B: Add vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stir at 110°C for 1.5 h, then transfer to a reactor equipped with a vacuum pump, increase the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, keep at 200°C for 3 h, cool to room temperature, and then transfer back to the four-necked flask; then, under the protection of dry nitrogen, slowly add isophorone diisocyanate, organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine dropwise to the four-necked flask, raise the temperature to 80°C after the addition is complete, keep for 3 h, then cool to room temperature, and obtain a silane-modified terminal isocyanate prepolymer; wherein the organic bismuth metal catalyst is tributyl; C. Component A and component B are uniformly mixed to obtain an antibacterial solvent-free coating.
[0051] The VOC emission of the coating prepared in this embodiment is less than 20g / L (national standard 100g / L, GB30981-2020).
[0052] Example 2 This embodiment is based on Example 1, and the difference from Example 1 is that the mass ratio of component A to component B in this embodiment is 2:1. The rest is the same as Example 1. The VOC emission of the coating prepared in this embodiment is less than 20g / L (national standard 100g / L, GB30981-2020).
[0053] Example 3 This embodiment is based on Example 1, and the difference from Example 1 is that the mass ratio of component A to component B in this embodiment is 2.4:1. The rest is the same as Example 1. The VOC emission of the coating prepared in this embodiment is less than 20g / L (national standard 100g / L, GB30981-2020).
[0054] Example 4 This embodiment is based on the embodiment 1, and is different from the embodiment 1 in that the component A in this embodiment includes the following components in parts by weight: 45 parts of vegetable oil-based modified polyol, 0.5 parts of antibacterial agent, 20 parts of color filler, and 4 parts of film-forming aid; The pigment filler in component A includes the following components in parts by weight: 15 parts of titanium dioxide with a particle size of 800 mesh, 5 parts of talc with a particle size of 3000 mesh, and 5 parts of heavy calcium with a particle size of 1250 mesh; The film-forming aid comprises the following components in parts by weight: 0.2 parts of an organosilicon defoamer, 1 part of a wetting and leveling agent, 1 part of a dispersant, 2 parts of a retarder, and 1.5 parts of an adhesion promoter; The component A is prepared by the following method: placing a vegetable oil-based modified polyol and a dispersant in a high-speed disperser, mechanically stirring for 10 minutes at a speed of 500 r / min, then slowly dropping an organic defoamer into the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser, mechanically stirring for 90 minutes at a speed of 1200 r / min, the slurry temperature being 50° C. during the stirring process, then adding a wetting and leveling agent, a retarder, and an adhesion enhancer, mechanically stirring for 30 minutes at a speed of 500 r / min, obtaining a crude product, and then filtering the crude product through a 150-mesh gauze and packaging to obtain component A.
[0055] The rest is the same as Example 1. The VOC emission of the coating prepared in this example is less than 20 g / L (national standard 100 g / L, GB30981-2020).
[0056] Example 5 This embodiment is based on the embodiment 1, and is different from the embodiment 1 in that the component A in this embodiment includes the following components in parts by weight: 62.5 parts of vegetable oil-based modified polyol, 1 part of antibacterial agent, 30 parts of pigments and fillers, and 6 parts of film-forming aids; The pigment filler in component A includes the following components in parts by weight: 25 parts of titanium dioxide with a particle size of 800 mesh, 15 parts of talc with a particle size of 3000 mesh, and 15 parts of heavy calcium with a particle size of 1250 mesh; The film-forming aid comprises the following components in parts by weight: 0.4 parts of an organosilicon defoamer, 2 parts of a wetting and leveling agent, 2.5 parts of a dispersant, 3.5 parts of a retarder, and 3 parts of an adhesion promoter; The component A is prepared by the following method: placing a vegetable oil-based modified polyol, a vegetable oil-based plasticizer, and a dispersant in a high-speed disperser, mechanically stirring for 8 minutes at a speed of 600 r / min, then slowly dropping an organic defoamer into the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talcum powder, and heavy calcium to the disperser, mechanically stirring for 70 minutes at a speed of 1300 r / min, the slurry temperature during the stirring process is 50°C, then adding a wetting and leveling agent, a retarder, and an adhesion enhancer, mechanically stirring for 20 minutes at a speed of 600 r / min, to obtain a crude product, and then filtering the crude product through a 150-mesh gauze and packaging to obtain component A. The VOC emission of the coating prepared in this embodiment is less than 20 g / L (national standard 100 g / L, GB30981-2020).
[0057] Comparative Example 1 This comparative example is based on Example 1, and the difference from Example 1 is that the mass ratio of component A to component B in this comparative example is 1.8:1. The rest is the same as Example 1.
[0058] Comparative Example 2 This comparative example is based on Example 1, and the difference from Example 1 is that the mass ratio of component A to component B in this comparative example is 2.5:1. The rest is the same as Example 1.
[0059] Comparative Example 3 This comparative example is based on Example 1, and is different from Example 1 in that no intermediate carrier is added to the composite antibacterial agent of this comparative example, and there is no need to prepare an intermediate carrier (microsphere). The preparation method of the composite antibacterial agent in this comparative example is as follows: weigh nano-scale zinc-loaded hydroxyapatite and ammonium cerium nitrate-modified nano-TiO2 in a mass ratio of 3:2, put them into an anhydrous ethanol solution, and after ultrasonic dispersion, repeatedly wash with deionized water and ethanol to obtain the composite antibacterial agent of this comparative example.
[0060] Comparative Example 4 This comparative example is based on Example 1, but is different from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier in the composite antibacterial agent of this comparative example is 2:2:5.
[0061] Comparative Example 5 This comparative example is based on Example 1, but is different from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier in the composite antibacterial agent of this comparative example is 1:2:5.
[0062] Comparative Example 6 This comparative example is based on Example 1, but is different from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier in the composite antibacterial agent of this comparative example is 3:2:4.
[0063] Comparative Example 7 This comparative example is based on Example 1, but is different from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier in the composite antibacterial agent of this comparative example is 3:2:6.
[0064] Comparative Example 8 This comparative example is based on Example 1, but is different from Example 1 in that the mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier in the composite antibacterial agent of this comparative example is 4:2:5.
[0065] Comparative Example 9 This comparative example is based on Example 1, but different from Example 1 in that 3-(acryloyloxy)propyltrimethoxysilane is not used to modify the surface of the microspheres in the composite antibacterial agent of this comparative example, and only a photosensitive compound is used to modify the surface of the microspheres, and the steps are: dissolving the photosensitive compound in chloroform to obtain a photosensitive compound solution, then immersing the microspheres in the photosensitive compound solution, reacting for 7-8 hours at room temperature, filtering and drying to obtain solid microspheres with pores distributed on the surface after surface modification by the photosensitive compound, wherein the solid microspheres with pores distributed on the surface after surface modification are intermediate carriers; wherein the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system.
[0066] Comparative Example 10 This comparative example is based on Example 1, and is different from Example 1 in that the composite antibacterial agent of this comparative example does not use a photosensitive compound to modify the microspheres, but only uses 3-(acryloxy)propyltrimethoxysilane for modification. The specific steps are: 3-(acryloxy)propyltrimethoxysilane is configured as a silane coupling agent solution with a mass fraction of 1.2%, and then solid microspheres with pores distributed on the surface are immersed in the silane coupling agent solution, and the microspheres are taken out after keeping for 2 hours and dried at 60°C for 1 hour to obtain microspheres modified by the silane coupling agent.
[0067] Comparative Example 11 This comparative example is based on Example 1, but is different from Example 1 in that the composite antibacterial agent of this comparative example does not use photosensitizing compounds and 3-(acryloyloxy)propyltrimethoxysilane to modify the surface of the microspheres.
[0068] Comparative Example 12 This comparative example is based on Example 1, and the difference from Example 1 is that polyethylene glycol and calcium sulfate are not added in the process of preparing microspheres in the composite antibacterial agent of this comparative example. The cross-sectional SEM scanning electron microscope image of the solid microspheres prepared in this comparative example is as follows: Figure 4 As shown, compared Figure 2 and Figure 4 It can be seen that there are a lot of voids inside the microspheres without adding polyethylene glycol and calcium sulfate. The presence of a lot of voids inside the microspheres will affect the antibacterial properties of the coating.
[0069] Test Example 1 According to the requirements of GB / T 21866-2008 standard, the antibacterial rate of the antibacterial coatings prepared in Examples 1-5 and Comparative Examples 1-12 was tested; the nano-scale zinc-loaded hydroxyapatite targets common bacteria, such as Escherichia coli and Staphylococcus aureus, and the ammonium cerium nitrate modified nano-TiO2 mainly produces free radicals through photocatalysis to fight bacteria, which requires light conditions when used; therefore, this test example measures the antibacterial rate of the antibacterial coatings prepared in Examples 1-5 and Comparative Examples 1-12 under light and no light conditions according to GB / T 21866-2008 standard. The antibacterial rate under light conditions is antibacterial rate 1, and the antibacterial rate without light conditions is antibacterial rate 2, and the results are shown in Table 1.
[0070] Test method: strain: Staphylococcus aureus; control sample: coating test plate without adding antibacterial ingredients (solvent-free coating prepared without adding antibacterial components according to the ratio and preparation method of Example 1); antibacterial coating test plate: coating test plate of antibacterial coating prepared by Examples 1-5 and Comparative Examples 1-12; inoculate bacteria uniformly on the test sample plate by quantitative inoculation method, cover with sterilization cover film after inoculation, so that bacteria are evenly in contact with the sample plate; place in a constant temperature incubator for 24 hours, culture conditions are 37°C, relative humidity is 90%, and culture is carried out under two lighting conditions, namely, under lighting and no lighting (according to the above method, it is carried out under lighting and no lighting conditions, and fluorescent light can be used); after taking out the sample plate, rinse it thoroughly with eluent, dilute it and count the viable bacteria culture by pouring method, and calculate the antibacterial rate according to the number of viable bacteria; Inhibition rate = (number of colonies in the control sample - number of colonies in the experimental sample) / number of colonies in the control sample × 100%; Control sample colony count: refers to the colony count obtained by counting live bacteria culture after a certain period of time (such as 24 hours) after inoculation of the sample plate that has not been treated with antimicrobial agents (i.e., the control sample); Colony count of experimental sample: refers to the colony count obtained under the same inoculation and culture conditions of the sample plate (i.e., experimental sample) after antibacterial treatment; Level I requirement is ≥99.00%, and Level II requirement is ≥90.00% (less than 99.00%); for example, if the number of viable bacteria after inoculation of the blank control sample is 10,000 cfu (colony forming units) / piece, and the number of viable bacteria after inoculation of the antibacterial sample is 100 cfu / piece, the antibacterial rate is calculated as follows: Antibacterial rate = (10,000 - 100) / 10,000 × 100% = 99%, which meets the requirements of Level I products.
[0071] During the test, the same batch of coatings will correspond to multiple coating test plates. Therefore, the larger the span between the maximum antibacterial rate and the minimum antibacterial rate, the more uneven the antibacterial performance distribution is. In Examples 1-5, the maximum difference in antibacterial rate under illumination conditions and under no illumination conditions is 0.003%, which is very small, indicating that the antibacterial performance distribution of the present invention is relatively uniform. Combined with the data in Table 1, Example 1 of the present invention is the best preparation method, the prepared solvent-free antibacterial coating has good antibacterial performance and uniform antibacterial performance distribution, and the VOC emission of the solvent-free antibacterial coating prepared in Example 1 is less than 20g / L (national standard 100g / L, GB30981-2020), the wear resistance of the coating film is 6 times that of the national standard (national standard ≤0.03g, this product ≤0.005g, GB / T22374-2018), and the combustion performance reaches the non-flammable A (A2-s1, t0) level (GB8624-2012).
[0072] Test Example 2 The antibacterial coatings prepared in Example 1 and Comparative Example 3 were used as experimental samples. According to the detection method of Test Example 1, 30 identical coating test plates were prepared from the antibacterial coating prepared in Example 1. Similarly, 30 identical coating test plates were prepared from the antibacterial coating prepared in Comparative Example 3. The above 60 coating test plates were placed in a constant temperature incubator for 24 hours under the incubation conditions of 37°C, 90% relative humidity, and light. The antibacterial rates of the 60 coating test plates were calculated according to Test Example 1. The maximum antibacterial rate and the minimum antibacterial rate of the 30 antibacterial coating test plates corresponding to Example 1 were calculated. The difference in the maximum antibacterial rate is recorded as the first difference; at the same time, the difference between the maximum antibacterial rate and the minimum antibacterial rate in the antibacterial coating test plates corresponding to 30 comparative examples 3 is calculated and recorded as the second difference; the first difference is 0.001%, and the second difference is 1.13%; the greater the difference between the maximum antibacterial rate and the minimum antibacterial rate in the antibacterial coating test plates of the same coating, the more uneven the antibacterial distribution of the coating; therefore, the uniformity of the antibacterial property of the coating prepared in Example 1 of the present invention is higher than that of the coating prepared in Comparative Example 3; it indicates that the antibacterial property of the composite antibacterial agent with the addition of an intermediate carrier is more uniform.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. An antibacterial solvent-free coating, characterized in that: Comprising component A and component B; The component A comprises the following components in parts by weight: 45-70 parts of vegetable oil-based modified polyol, 0.5-1.5 parts of antibacterial agent, 20-40 parts of pigment and filler, and 4-8 parts of film-forming aid; The component B is a silane-modified terminal isocyanate prepolymer; The mass ratio of component A to component B is (2~2.4):1; The antibacterial agent in component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate, and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; The mass ratio of nano-scale zinc-loaded hydroxyapatite, ammonium cerium nitrate-modified nano-TiO2 and the intermediate carrier is 3:2:5; The surface porosity of the microspheres is 30%-60%, the particle size D90 of the microspheres is 10-15 μm, the particle size D90 of nano-grade zinc-loaded hydroxyapatite and ammonium cerium nitrate modified nano-TiO2 are both 50-80 nm, and the pore size of the microsphere surface pores is 50-100 nm.
2. The antibacterial solvent-free coating according to claim 1, characterized in that: The composite antibacterial agent is prepared by the following method: S1. Preparation of intermediate carrier S1.1, preparation of solid microspheres: polylactic acid-polymethyl methacrylate block copolymer and polyethylene glycol are dissolved in dichloromethane, and calcium sulfate is added after stirring evenly, and stirred evenly to obtain a polymer solution; the polymer solution is slowly added dropwise to the aqueous phase containing polyvinyl alcohol, and emulsified by ultrasonic emulsifier at room temperature to form a stable O / W type emulsion; the O / W type emulsion is placed at 30-40°C to volatilize the solvent, and when the solvent is completely volatilized, the microspheres are separated from the emulsion by a centrifuge, the microspheres are washed with deionized water for multiple times, and then dried to obtain solid microspheres; S1.2, surface pore formation: soak the solid microspheres in phosphoric acid etchant, etch at 25°C for 30-40 minutes, wash and dry to obtain solid microspheres with pores distributed on the surface; S1.3, microsphere surface modification: firstly prepare 3-(acryloxy)propyltrimethoxysilane into a silane coupling agent solution with a mass fraction of 1.2%, then immerse the solid microspheres with pores on the surface into the silane coupling agent solution, keep for 2 hours, take out the microspheres and dry them at 60°C for 1 hour to obtain microspheres modified by the silane coupling agent; The photosensitive compound is dissolved in chloroform to obtain a photosensitive compound solution, and then the microspheres modified with a silane coupling agent are immersed in the photosensitive compound solution, reacted at room temperature for 7-8 hours, filtered and dried to obtain solid microspheres with pores on the surface after surface modification by 3-(acryloyloxy)propyltrimethoxysilane and the photosensitive compound, wherein the solid microspheres with pores on the surface after surface modification are intermediate carriers; wherein the photosensitive compound is 8-methoxy-psoralen, and the amount of 8-methoxy-psoralen added is 0.8% of the total mass of the microspheres in the reaction system; S2, preparing nano-scale zinc-loaded hydroxyapatite; S3, preparing ammonium cerium nitrate modified nano-TiO2; S4. Place nano-TiO2 modified by ammonium cerium nitrate and nano-zinc-loaded hydroxyapatite in anhydrous ethanol solution, disperse by ultrasonication to form a uniform suspension, add the intermediate carrier into the suspension, stir continuously for 10-12 hours at 30°C, filter and dry to obtain microspheres with nano-zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate adsorbed on the surface, which is the composite antibacterial agent.
3. The antibacterial solvent-free coating according to claim 2, characterized in that: The amount of polyethylene glycol added is 5% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, the amount of calcium sulfate added is 1% of the mass of the polylactic acid-polymethyl methacrylate block copolymer, and the concentration of polyvinyl alcohol is 0.5wt%.
4. The antibacterial solvent-free coating according to claim 2, characterized in that: The phosphoric acid etchant is composed of the following components in mass fractions: 25% phosphoric acid, 58% citric acid, 1% surfactant, and the balance is deionized water.
5. The antibacterial solvent-free coating according to claim 1, characterized in that: The preparation method of the nano-scale zinc-loaded hydroxyapatite is as follows: calcium nitrate, disodium hydrogen phosphate and titanium sulfate are used to prepare hydroxy titanium phosphate through a coprecipitation reaction, and then zinc ions and hydroxy titanium phosphate are used to prepare the nano-scale zinc-loaded hydroxy titanium apatite through an ion exchange method.
6. The antibacterial solvent-free coating according to claim 1, characterized in that: The ammonium cerium nitrate modified nano-TiO2 is prepared by the following method: adding appropriate amounts of anhydrous ethanol, hydrochloric acid and butyl titanate into a three-necked flask, and then ultrasonically dispersing for 30 minutes to form a titanium source solution; Dissolving ammonium cerium nitrate in ethanol and stirring evenly to obtain a modifier solution; Under stirring conditions, the modifier solution is slowly added to the titanium source solution, and the mixture is stirred at a speed of 500-800 r / min for 2-4 hours to obtain a transparent sol. After the transparent sol is dried and ground, it is calcined at 800°C for 5 hours in a nitrogen atmosphere to obtain ammonium cerium nitrate modified nano-TiO2.
7. The antibacterial solvent-free coating according to claim 1, characterized in that: The component B is prepared by the following method: adding a vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stirring at 90-120° C. for 1-2 h, then transferring to a reactor equipped with a vacuum pump, increasing the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, maintaining at 180-220° C. for 2-3 h, cooling to room temperature, and then transferring back to the four-necked flask; subsequently, stirring under the protection of dry nitrogen, slowly dropping isophorone diisocyanate, an organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine into the four-necked flask, raising the temperature to 60 to 90° C. after the addition is complete, maintaining for 2-3 h, then cooling to room temperature, and discharging to obtain a silane-modified terminal isocyanate prepolymer.
8. The antibacterial solvent-free coating according to claim 1, characterized in that: The pigment filler in component A includes the following components in parts by weight: 15-25 parts of titanium dioxide with a particle size of 800 mesh, 5-15 parts of talc with a particle size of 3000 mesh, and 5-15 parts of heavy calcium with a particle size of 1250 mesh; The film-forming aid comprises the following components in parts by weight: 0.2-0.4 parts of an organosilicon defoamer, 1-2 parts of a wetting and leveling agent, 1-2.5 parts of a dispersant, 2-3.5 parts of a retarder, and 1.5-3 parts of an adhesion promoter; The component A is prepared by the following method: placing a vegetable oil-based modified polyol and a dispersant in a high-speed disperser, mechanically stirring for 5-10 minutes at a speed of 500-700 r / min, then slowly dropping an organic defoamer into the mixture, continuing to stir and mix in the high-speed disperser for 10 minutes, then sequentially adding an antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser, mechanically stirring for 50-90 minutes at a speed of 1200-1500 r / min, wherein the slurry temperature does not exceed 60° C. during the stirring process, then adding a wetting and leveling agent, a retarder, and an adhesion enhancer, mechanically stirring for 10-30 minutes at a speed of 500-700 r / min, obtaining a crude product, and then filtering the crude product through a 150-mesh gauze and packaging it to obtain component A.
9. The antibacterial solvent-free coating according to claim 8, characterized in that: Comprising component A and component B; The component A comprises the following components in parts by weight: 70 parts of vegetable oil-based modified polyol, 1.5 parts of antibacterial agent, 40 parts of pigment and filler, and 8 parts of film-forming aid; The component B is a silane-modified terminal isocyanate prepolymer; the mass ratio of component A to component B is 2.2:1; The antibacterial agent in the component A is a composite antibacterial agent, which includes nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and an intermediate carrier; the intermediate carrier is a microsphere with pores distributed on the surface, and the nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are simultaneously adsorbed on the surface of the microsphere to obtain the composite antibacterial agent; the mass ratio of nano-scale zinc-loaded hydroxyapatite, nano-TiO2 modified by ammonium cerium nitrate and the intermediate carrier is 3:2:5; the surface porosity of the microsphere is 30%-60%, the particle size D90 of the microsphere is 10-15μm, the particle size D90 of nano-scale zinc-loaded hydroxyapatite and nano-TiO2 modified by ammonium cerium nitrate are both 50-80nm, and the pore size of the pores on the surface of the microsphere is 50-100nm; The film-forming aid comprises the following components in parts by weight: 0.3 parts of an organosilicon defoamer, 1.5 parts of a wetting and leveling agent, 1.5 parts of a dispersant, 2.5 parts of a retarder, and 2 parts of an adhesion promoter; The pigments and fillers in component A include the following components in parts by weight: 20 parts of titanium dioxide with a particle size of 800 mesh, 10 parts of talc with a particle size of 3000 mesh, and 10 parts of heavy calcium with a particle size of 1250 mesh.
10. A method for preparing an antibacterial solvent-free coating according to any one of claims 1 to 9, characterized in that: The steps include: A. Synthesis of component A: Place the vegetable oil-based modified polyol and dispersant in a high-speed disperser, stir mechanically for 5-10 minutes at a speed of 500-700 r / min, then slowly drop the organic defoamer into the mixture, continue to stir and mix in the high-speed disperser for 10 minutes, then add the antibacterial agent, titanium dioxide, talcum powder, and heavy calcium into the disperser in sequence, stir mechanically for 50-90 minutes at a speed of 1200-1500 r / min, the slurry temperature does not exceed 60°C during the stirring process, then add the wetting and leveling agent, retarder, and adhesion enhancer, stir mechanically for 10-30 minutes at a speed of 500-700 r / min to obtain a crude product, and then filter the crude product through a 150-mesh gauze and package it to obtain component A; B. Synthesis of component B: Add the vegetable oil-based modified polyol to a four-necked flask equipped with a stirrer and a thermometer, stir at 90-120°C for 1-2 h, transfer to a reactor equipped with a vacuum pump, increase the vacuum degree to -0.08 to -0.12 MPa at a rate of -0.02 MPa / h, keep at 180-220°C for 2-3 h, cool to room temperature, and transfer back to the four-necked flask; then, stir under the protection of dry nitrogen, slowly drop isophorone diisocyanate, organic bismuth metal catalyst, N-ethyl-3-trimethoxysilane-2-methylpropylamine, and bis-(γ-trimethoxysilylpropyl)amine into the four-necked flask, raise the temperature to 60 to 90°C after the addition is complete, keep for 2-3 h, then cool to room temperature, and discharge the material to obtain a silane-modified terminal isocyanate prepolymer; C. Component A and component B are uniformly mixed to obtain an antibacterial solvent-free coating.
Citation Information
Patent Citations
Nanoporous coating of titanium dioxide on titanium alloy and the method of manufacturing
EP3632479A1
Compositions, uses and synthetic method of afunctional nanohydroxy apatite and that derivatives
KR1020060100505A
Antimicrobial Devices and Compositions
US20090035342A1
Method for preparing polyurethane coating and adhesive with antibacterial and waterproof properties
WO2016109910A1
Cited By
Silver monatomic antibacterial and antiviral material as well as preparation method and application thereof
CN121195972A
Silver monatomic antibacterial and antiviral material, and preparation method and application thereof
CN121195972B
Antibacterial coating for vehicle chassis and preparation method thereof
CN122011855A
